2023
DOI: 10.1002/pon.6184
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioral symptoms in patients with melanoma: A systematic review and meta‐analysis

Abstract: ObjectiveImproved survival rates have made it increasingly important for clinicians to focus on cancer survivorship issues affecting the quality of life of melanoma patients. To provide a comprehensive overview of the disease and treatment‐related issues affecting such patients, we conducted a systematic review and meta‐analysis of the literature to estimate the prevalence of symptoms of depression, anxiety, fatigue, sleep disturbance, and cognitive problems among melanoma patients, both uveal and cutaneous, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…The psychological impact of subungual melanoma on patients and their families is significant. Anxiety and depression are common in patients with melanoma before, during and after treatment [ 14 ]. It is crucial for healthcare providers to recognize the potential psychological impact of SUM and offer the necessary support to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological impact of subungual melanoma on patients and their families is significant. Anxiety and depression are common in patients with melanoma before, during and after treatment [ 14 ]. It is crucial for healthcare providers to recognize the potential psychological impact of SUM and offer the necessary support to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Attentional Control Scale (ACS; [33]) is a 20-item self-report instrument assessing an individual's ability to focus and shift attention. Participants responded to 8 positively worded statements of everyday attention (4, 5, 9, 10, 13, 14, 17, 19, e.g., it is easy for me to read or write while I'm also talking on the phone) and 12 negatively worded statements (1,2,3,6,7,8,11,12,15,16,18,20, e.g., When I am working hard on something, I still get distracted) on a 4-point scale of 1 = almost never to 4 = always. Total scores ranged from 20 to 80, with higher scores reflecting better attentional control.…”
Section: Attentional Control Scalementioning
confidence: 99%
“…Cognitive problems such as attention and concentration difficulties are also reported in the broader cancer survivorship literature [10,11], including investigations with melanoma patients [12]. Studies with healthy participants have shown that heightened anxiety is related to attention and memory deficits [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…Psychiatric conditions such as depression and anxiety are a frequent occurrence in patients diagnosed with late-stage cancer [1,2]. Conversely, surgeons treating locally advanced tumors sometimes discover that their patients have in fact long been treated for psychiatric disorders, which turn out to have been the first manifestations of metastatic brain disease stemming from a yet undiagnosed cancer.…”
Section: Introductionmentioning
confidence: 99%